INVESTIGATIONS ON SEASONAL ABUNDANCE OF THE EARTHWORM OCTOLASION CYANEUM (SAVIGNY, 1826) (LUMBRICIDAE: ANNELIDA) IN HIGH ALTITUDE FOREST SYSTEM OF THE KUMAUN HIMALAYAS, INDIA: Life Sciences-Zoology - NEHA RAJWAR; SATPAL SINGH BISHT; SPARSH BHATT; RASHI MIGLANI; VINAY SINGH (International Journal of Life Science and Pharma Research, 2022)
The study was conducted in Nainital 29°23′27.94′′ N, 79°26′53.34′′ E at 2046 m a.s.l. and describes the population dynamics of earthworm Octolasion cyaneum (Lumbricidae: Annelida) during three seasons i.e. summer (March-June), rainy (July-October) and winter (November-February) to determine the density of earthworm Octolasion cyaneum and its relationship with climatic and physico-chemical factors of soil. The area is inhabited by the earthworm Octolasion cyaneum which has been reported first time in the Kumaun region of Uttarakhand, India and is considered as the inhabitant of higher altitudes of Indian Himalayas. A mean total of 2550 earthworms from 6 field collections were collected in two consecutive study years i.e. 2015-17. The mean density of earthworm ranged between 10 m-2 to 48.25 m-2 during the study period. The study showed that the maximum density of earthworm was recorded in the upper monolith (0-15 cm) as the organic content is more abundant in upper strata. The age structure of earthworms indicated that the clitellates were more abundant than aclitellates. The mean soil pH from the forest sample was slightly acidic i.e. 6.5 and C: N has been found 11.3. A significant positive correlation has been obtained between worm density and soil temp (r<0.05) and soil C (r<0.05).